Supramolecular Metallacycles and Their Binding of Fullerenes. Issue 16 (5th March 2020) - Göb, Christian R.; Ehnbom, Andreas; Sturm, Lisa; Tobe, Yoshito; Oppel, Iris M.
Abstract: The synthesis of a new triaminoguanidinium‐based ligand with three tris ‐chelating [NNO]‐binding pockets and C 3 symmetry is described. The reaction of tris ‐(2‐pyridinylene‐ N ‐oxide)triaminoguanidinium salts with zinc(II) formate leads to the formation of cyclic supramolecular coordination compounds which in solution bind fullerenes in their spherical cavities. The rapid encapsulation of C60 can be observed by NMR spectroscopy and single‐crystal X‐ray diffraction and is verified using computation. Abstract : Cage bound : Synthesis of a new triaminoguanidinium‐based ligand with three tris ‐chelating [NNO] binding pockets and C 3 ‐symmetry is described. Reaction with zinc(II) formate leads to the formation of cyclic supramolecular coordination compounds that in solution are able to bind fullerenes in their spherical cavities. The rapid encapsulation of C60 is observed by NMR spectroscopy and X‐ray diffraction and is validated by DFT.